Time management and velocity profiles in elite triple jumping - Niessen, J.; Jürgens, A.; Unger, J.; Burgardt, K.; Hartmann, U. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The achieved distances in triple jump (TJ) strongly dependent upon the available horizontal velocity in run-up and each of the take-offs (TO). Kinetic energy is produced through the approach speed in every TO and is converted into height and distance. Due to less information in literature, the aim of our competition accompanying project is to detect velocity profiles and individual time managements (TM) in different performance levels, techniques and between ender. Methods Within a scientific project and in cooperation with the German Athletic Association (DLV), we analysed up to 435 competition-velocity profiles (CVP) (e.g. international Meetings (2002, 2003) German (GCh) (2002, 2003) and European Championships (ECh) 2002) of 37 male and 30 female elite triple jumpers during the outdoor-season. The run-up and jumps were registered by a laser velocity (Laveg) measurement system (LDM 300C (Jenoptik, Jena)), placed in approach direction to measure the distance between the laser detector and the reflecting object (100 Hz). To determine instant speed values throughout run-up until land in the pit, the laser beams were directed on the lower back of the athlete. The raw data and the calculated speed curves (67pt moving average of distance and speed) were registered real-time and stored in a PC (software: Sport 3.9 (Jenoptik, Jena), LavegDrei (Huber, Munich) and AdGraph (Basis, Munich)). Additionally a professional digital video camera (CANON XM-1 (Canon, Japan)) was placed perpendicular to the H-S transition in order to capture the side movement of the plane of motion. 2D-kinematic analysis (e.g. stride pattern (SP), calculation of selected phase distances (PD)) was performed with DartTrainerPro 2.5.3 (Dartfish, Fribourg) (Niessen et al. 2003). Results World class performances in TJ reached peak velocity values in run-up (vmax) of > 10.2 m s-1 in men (TJ > 17 m) and > 9.1 m s-1 in women (TJ > 14.5 m). Further results of male and female TJ pointed out significant correlations between run-up velocity indices (VI) (p.0.001) and effective distance (official plus toe-to-board) as well as second last stride (p.0.05). High significant differences were observed for CVP indices in run-up and TOPH as well as for TM indices in run-up (15-2m (men (m) and 15-0m (women (w) prior to board and hop-step transition between high m: >16.5m; w: >14m) and low (m: <16.5m; w: <14m) level TJ (Tab. 1) Discussion/Conclusion In summary time management profiles were similarly in male and female elite TJ, but point out significant differences in run-up and hop to step between high and low level TJ. CVP behaviour was analogue in both gender, but inter-individual (Delta up to 12%) and intra-individual (Range: 0-12%) different. High level TJ achieved higher velocities prior to board due to the stride pattern "long-short" (2nd and last stride) as well as short contact times during H-S transition. Horizontal velocity drops during TOP hop, step and jump (Hay 1992) were higher in male (-1 m s-1) than female (-0.7 m s-1) TJ due to larger phase distances (Niessen et al. 2003). In conclusion high vmax, scarcely loss of horizontal velocity in TOPH and Trans H-S are important factors for top level TJ distances in particular.